The Influence of Clove Leaf Size Variations on the Characteristics of Clove Leaf Essential Oil Production - Raharjo; Caroko Novi; Angga Sutopo Tegar (BIO Web of Conferences)
Clove leaves are waste products from clove plantations in Kulon Progo, Yogyakarta. Most clove utilization is limited to the buds, while clove leaves have the potential to be a source of essential oil. Essential oil from clove leaves can be extracted using steam-water distillation. One factor influencing the characteristics of clove leaf essential oil production is the variation in material size. In this study, essential oil extraction was conducted using the steam-water distillation method with different clove leaf sizes, namely 2 cm, 3 cm, 4 cm, and 5 cm. The differences in clove leaf size were intended to determine the most suitable leaf size for extraction using the steam-water distillation method. This study showed that a clove leaf size of 2 cm produced a volume and yield of clove leaf oil of 53.5 ml and 5.45%, respectively. The density value of clove leaf oil obtained from this study was 1.019 grams/mL. The clove leaf oil produced was clear yellowish and had the characteristic aroma of clove oil. These criteria meet SNI 06-2378-2006 for clove leaf oil.